Pelatihan Pengelolaan Website Desa Sebagai Media Informasi Digital Di Desa Fafinesu C, Kecamatan Insana Fafinesu, Kabupaten Timor Tengah Utara - Yoseph PK. Kelen; Anastasia Kadek Dety Lestari; Siprianus Septian Manek; Kristoforus Fallo (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2022)
Digital information media allows the disclosure of public information and supports development. Website as a digital information media is an important way to be developed especially in the field of Government. Content Management System (CMS) is an alternative website creation without using programming. To facilitate village operators in creating and managing village information digitally, training of village website management as an information media is an important thing to do. Fafinesu C village at Insana Fafinesu District, North Central Timor Regency is the target in this program. The problems in Fafinesu C village are information system of village has not been managed properly, the absence of villace information system and the village officials still not understand about management information. The program is collaboration with Insana Fafinesu Subdistrict and Fafinesu C village. With this program, village operators can create a village website using a CMS. Website of Fafinesu C villages can publish the information about the village. The operator of village can manage the website independently. In addition, through the village website, village potentials can be published so that the village are able to develop the potential that exist.